A Novel Poly(Glutaraldehyde-co-Pyrrole)/Horseradish Peroxidase Composite Film Electrode - Ozoner, Seyda Korkut; Can, Mevra Yalvac; Keskinler, Bulent; Erhan, Elif (TAYLOR & FRANCIS INC, 2009)
A newly synthesized copolymer, Poly(glutaraldehyde-co-pyrrole) was used to immobilize horseradish peroxidase for the construction of an amperometric biosensor for detection of phenols in a flow injection system. Infrared spectra of Poly(glutaraldehyde-co-pyrrole) showed that the incorporation of aldehyde groups into the conductive polymeric backbone was achieved. The [image omitted] values were found to be in the range of 0.077-0.468mM for p-benzoquinone and 0.112-0.709mM for catechol, at various flow rates ranging between 0.25-6mL/min. The sensitivities at various flow rates ranged between 100-200nA/mM for catechol and 30-100nA/mM for p-benzoquinone. The biosensor retained its initial activity for 1 month.
Keywords: Amperometric biosensor; p-benzoquinone; catechol; flow injection; poly(glutaraldehyde); poly(pyrrole); CONDUCTING POLYMERS; TYROSINASE; IMMOBILIZATION; LACCASE; POLYPYRROLE; Chemistry